1994
DOI: 10.1051/rnd:19940508
|View full text |Cite
|
Sign up to set email alerts
|

Preserved bone mass in ovariectomized rats treated with parathyroid-hormone-related peptide (1-34) and (107-111) fragments

Abstract: Summary ― The effect of synthetic human PTHrP (1 -34) or (107-111) fragments on bone loss was studied in rats, one month after ovariectomy (OVX). Four groups of 7-8-month-old rats were treated sc daily for 13 d with PTHrP (1-34) or (107)(108)(109)(110)(111) at the dose of 1 or 3 nmol/100 g body weight. Sham-operated (SHO) and control OVX rats received solvent alone. In our conditions, at the lowest dose, neither (1-34) nor (107-111 ) fragments had any significant effect. However, at the dose of 3 nmol/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
(25 reference statements)
3
14
0
Order By: Relevance
“…In any event, the true role of this C-terminal PTHrP domain in bone is unclear. An early study showed that daily administration of osteostatin for 2 weeks to ovariectomized rats prevented bone loss in femur and tibia, apparently at the expense of a positive effect in cortical bone [4]. Very recently, we found that an equivalent dose of PTHrP (107e139) than that used for osteostatin in the latter study reversed the cortical bone loss and improved bone regeneration after marrow ablation in mice undergoing 3-methylprednisolone administration [21].…”
Section: Introductionmentioning
confidence: 63%
“…In any event, the true role of this C-terminal PTHrP domain in bone is unclear. An early study showed that daily administration of osteostatin for 2 weeks to ovariectomized rats prevented bone loss in femur and tibia, apparently at the expense of a positive effect in cortical bone [4]. Very recently, we found that an equivalent dose of PTHrP (107e139) than that used for osteostatin in the latter study reversed the cortical bone loss and improved bone regeneration after marrow ablation in mice undergoing 3-methylprednisolone administration [21].…”
Section: Introductionmentioning
confidence: 63%
“…Moreover, a histomorphometric study in osteopenic rats treated daily for about 2 weeks with PTHrP (107-111), which accounts for the effects of PTHrP (107-139) in various cell types (11,13,15,17,(43)(44)(45), found a decreased trabecular bone formation associated with an increased bone resorption (46). Because, as stated above, NF-B activation appears to be a common mechanism of bone resorption activators in osteoblastic cells, our present findings further support that PTHrP (107-139) might be a stimulator of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The N‐terminal domain of PTHrP interacts with the PTH 1 receptor (PTH 1 R) in osteoblasts (Dean et al ., 2008). As shown to be the case with PTH, this domain is anabolic for bone when administered in an intermittent manner (Rouffet et al ., 1994; Stewart et al ., 2000; Horwitz et al ., 2003; Goltzman, 2008; Lozano et al ., 2009). In addition, recent studies strongly suggest that PTHrP domains other than its N‐terminal domain might contribute to the PTHrP role(s) in bone.…”
Section: Introductionmentioning
confidence: 95%